Spatiotemporally resolved imaging of streamer discharges in air generated in a wire-cylinder reactor with (sub)nanosecond voltage pulses. (4th July 2017) - Huiskamp, T; Sengers, W; Beckers, F J C M; Nijdam, S; Ebert, U; Heesch, E J M van; Pemen, A J M
Abstract: We use (sub)nanosecond high-voltage pulses to generate streamers in atmospheric-pressure air in a wire-cylinder reactor. We study the effect of reactor length, pulse duration, pulse amplitude, pulse polarity, and pulse rise time on the streamer development, specifically on the streamer distribution in the reactor to relate it to plasma-processing results. We use ICCD imaging with a fully automated setup that can image the streamers in the entire corona-plasma reactor. From the images, we calculate streamer lengths and velocities. We also develop a circuit simulation model of the reactor to support the analysis of the streamer development. The results show how the propagation of the high-voltage pulse through the reactor determines the streamer development. As the pulse travels through the reactor, it generates streamers and attenuates and disperses. At the end of the reactor, it reflects and adds to itself. The local voltage on the wire together with the voltage rise time determine the streamer velocities, and the pulse duration the consequent maximal streamer length.